The classification of algorithms for Privacy Management in Ubiquitous Environments - Leithardt, Valderi R. Q.; Rolim, Carlos O.; Rossetto, Anubis G. M.; Borges, Guilherme A.; Silva, Jorge Sá; Geyer, Claudio F. R. (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP), 2016)
Control and data management in ubiquitous environments is not a trivial activity owing to the heterogeneity of the users, applications and devices, required to exchange information. However, various problems have been found in the literature with regard to privacy information and related to the data used in ubiquitous environments. This paper offers a solution by means of statistical classification algorithms that can be used for control and privacy management. On the basis of the algorithms used in the tests, it proved to be possible to control and manage information by providing definitions of the variables and parameters for users, devices, and ubiquitous environments.